Effect of changing the outer fuel element diameter on thermophysical parameters of KLT-40S reactor unit - Belyavsky S. V. Sergey Vladimirovich; Alkhassan S. Samiru; Danilenko V. O. Vitaly Olegovich; Karvan R. A. Rodion Alekseevich; Nesterov V. N. Vladimir Nikolaevich (2023, 2023)
Title screen